2015
DOI: 10.1158/0008-5472.can-14-3499
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Intratumoral CCL22 by Type I Interferon Inhibits Migration of Regulatory T Cells and Blocks Cancer Progression

Abstract: The chemokine CCL22 is abundantly expressed in many types of cancer and is instrumental for intratumoral recruitment of regulatory T cells (Treg), an important subset of immunosuppressive and tumor-promoting lymphocytes. In this study, we offer evidence for a generalized strategy to blunt Treg activity that can limit immune escape and promote tumor rejection. Activation of innate immunity with Toll-like receptor (TLR) or RIG-I-like receptor (RLR) ligands prevented accumulation of Treg in tumors by blocking the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 45 publications
4
45
1
1
Order By: Relevance
“…immune cells can secrete CCL22, 38,39 in most other types of cancer, however, CCL22 is secreted by tumor-infiltrating immune cells. 40 In HCC, CCL22 upregulation was shown in HBVinfected HCC cell lines and HBVC primary HCC tumors on mRNA level. 35 In HCC, using immunohistology, we did not observe any CCL22 expression by tumor cells in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…immune cells can secrete CCL22, 38,39 in most other types of cancer, however, CCL22 is secreted by tumor-infiltrating immune cells. 40 In HCC, CCL22 upregulation was shown in HBVinfected HCC cell lines and HBVC primary HCC tumors on mRNA level. 35 In HCC, using immunohistology, we did not observe any CCL22 expression by tumor cells in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…18 C-C motif chemokine 22 (CCL22), also known as macrophage-derived chemokine, was found abundantly expressed in many types of malignancies. [19][20][21][22][23] Evidence obtained from studies suggested that CCL22-CCR4 signaling axis could help peritoneal tumors to migrate, survive, and establish cell cluster-type metastasis, in contrast to later stages of tumor development, in which CCL22 activation was needed. 24 Moreover, according to recent studies, tumor cells could transform CD4 C T cells into Tregs, resulting in high risk of immune escape.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmunity/inflammation disease: Tregs play an essential role in the prevention of autoimmune diseases and the maintenance of peripheral tolerance [1, 63] in cancer therapy [15, 64], transplantation tolerance [9, 19, 65, 66], inflammatory bowel disease [67], allergy/asthma [68, 69], liver disease [70], blood diseases [71], and dermatological diseases [72]. …”
Section: Resultsmentioning
confidence: 99%